Primary prevention for employees in the Information Age Organization. Issue 1 (March 2017) - Schellhammer, Stefan; Klein, Stefan; Ebner, Esther
Abstract: The nature of work and the way it is organized continues to change profoundly. The continuing debate on flexible work arrangements reveals the perceived need of policy makers to react to these changes in a balanced manner. Despite the demand of organizations and employees alike, the negative implications of flexible work arrangements threaten to counteract the equally valid arguments for their benefits. The new autonomy of the individual employee is mirrored by a management style that emphasizes results rather than specifying the way to achieve them. Despite the cherished liberties of the new workplace, studies indicate that stress due to unhealthy work practices has become a major concern for preventive care in these environments. Based on a study with IT professionals we set out to dispute the effectiveness of mainstream measures of preventive care that aim at (re-)regulating work. Instead, we propose an employee-centred approach to preventive care that aims at sensitizing employees to structural defects of new ways of working (through biofeedback and reflection on work patterns) and helping employees in crafting their work practices. Initial results of our empirical study, which combines biometric as well as qualitative data, indicate both the need and the potential for employee-centred preventive care. We demonstrate how bio feedback can inform the coaching of individuals in their quest for sustainable work practices.